2018
DOI: 10.1186/s13568-018-0556-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feedstock and co-culture of Lactobacillus fermentum and wild Saccharomyces cerevisiae strain during fuel ethanol fermentation by the industrial yeast strain PE-2

Abstract: Even though contamination by bacteria and wild yeasts are frequently observed during fuel ethanol fermentation, our knowledge regarding the effects of both contaminants together is very limited, especially considering that the must composition can vary from exclusively sugarcane juice to a mixture of molasses and juice, affecting the microbial development. Here we studied the effects of the feedstock (sugarcane juice and molasses) and the co-culture of Lactobacillus fermentum and a wild Saccharomyces cerevisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…Conversion of cellulose to bioethanol is a two-step process: saccharification and fermentation, respectively. The saccharification process is conducted at higher temperatures between 50 and 55 • C (which requires high energy and cost) (Murashima et al, 2002;Wang et al, 2009;Liu et al, 2016), while the ethanol fermentation using Saccharomyces cerevisiae occurs at lower temperatures between 25 and 30 • C (Borrull et al, 2016;Reis et al, 2018). Thus a cold-adaptive, endo-β-1,4-glucanase catalyzing the saccharification process under ambient temperatures could be of high significance.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of cellulose to bioethanol is a two-step process: saccharification and fermentation, respectively. The saccharification process is conducted at higher temperatures between 50 and 55 • C (which requires high energy and cost) (Murashima et al, 2002;Wang et al, 2009;Liu et al, 2016), while the ethanol fermentation using Saccharomyces cerevisiae occurs at lower temperatures between 25 and 30 • C (Borrull et al, 2016;Reis et al, 2018). Thus a cold-adaptive, endo-β-1,4-glucanase catalyzing the saccharification process under ambient temperatures could be of high significance.…”
Section: Introductionmentioning
confidence: 99%
“…This biotype of cell yeast morphology is also called snowflake [6]. Studies have shown that a wild S. cerevisiae strain exhibiting pseudohyphal morphology is often associated with lower ethanol production and higher residual sugar content in the fermented must [7,8]. In contrast, in the brewing and chemical manufacturing industry, pseudohyphal yeasts have been exploited to change flavour and aroma in beverage products and to produce acetic acid, respectively [9].…”
mentioning
confidence: 99%
“…The strain (originally termed 'strain 52') was identified by the sequencing of the D1/D2 region of the large subunit (26S) rRNA and deposited at the culture collection 'Coleção de Culturas Tropical' of 'Fundação André Tosello', Campinas-SP-Brazil under the code CCT7787. This yeast strain was utilized in previous studies of fermentation characteristics[5,7,8].…”
mentioning
confidence: 99%
“…A presença das bactérias contaminantes na dorna afeta o desempenho da cepa de levedura durante a fermentação industrial (BECKNER et al, CHANG et al, 1995;JOUHTEN et al, 2016;NARENDRANATH et al, 1997;REIS et al, 2018). Dentre os fatores estão, a produção de ácido lático e acético que diminuem o pH do meio e ainda, quando na forma não dissociada, os ácidos orgânicos difundem pela membrana celular ao meio intracelular, acidificando o citoplasma com a liberação de íons H + (BASSO et al, 2014;BECKNER et al, 2011;NARENDRANATH et al, 2001;REIS et al, 2018;THOMAS et al 2001 BECKNER et al, 2011).…”
Section: Interação Entre Lactobacillus E Saccharomyces Cerevisiaeunclassified
“…Durante a fermentação, os microrganismos contaminantes interagem de forma negativa com a cepa de levedura (BECKNER et al, 2011) em que as bactérias homo e heterofermentativas afetam de maneira distinta sua viabilidade e desempenho fermentativo (BASSO et al, 2014). Dentre os mecanismos envolvidos na interação, têm-se a produção pelas LAB de ácidos orgânicos e outros metabólitos (BECKNER et al, 2011;REIS et al, 2018), competição por substrato (LEROI e PIDOUX, 1993) e nutrientes (BAYROCK e INGLEDEW, 2004). Além disso, as bactérias ocasionam a floculação celular da levedura em decorrência da presença da manose em sua parede celular, fazendo com que ocorra a aglutinação entre as células e biofilme bacteriano, afetando a eficiência fermentativa da levedura (PRETZER et al, 2005).…”
Section: Introductionunclassified